Construct Validity and Minimal Important Difference of 6-Minute Walk Distance in Survivors of Acute Respiratory Failure - Chan, Kitty S. (Chest, 2015)
OBJECTIVE: The 6-min walk distance (6MWD), a widely used test of functional capacity, has limited evidence of construct validity among patients surviving acute respiratory failure (ARF) and ARDS. The objective of this study was to examine construct validity and responsiveness and estimate minimal important difference (MID) for the 6MWD in patients surviving ARF/ARDS. METHODS: For this secondary data analysis of four international studies of adult patients surviving ARF/ARDS (N = 641), convergent and discriminant validity, known group validity, predictive validity, and responsiveness were assessed. MID was examined using anchor- and distribution-based approaches. Analyses were performed within studies and at various time points after hospital discharge to examine generalizability of findings. RESULTS: The 6MWD demonstrated good convergent and discriminant validity, with moderate to strong correlations with physical health measures (|r| = 0.36-0.76) and weaker correlations with mental health measures (|r| = 0.03-0.45). Known-groups validity was demonstrated by differences in 6MWD between groups with differing muscle strength and pulmonary function (all P < .01). Patients reporting improved function walked farther, supporting responsiveness. 6MWD also predicted multiple outcomes, including future mortality, hospitalization, and health-related quality of life. The 6MWD MID, a small but consistent patient-perceivable effect, was 20 to 30 m. Findings were similar for 6MWD % predicted, with an MID of 3% to 5%. CONCLUSIONS: In patients surviving ARF/ARDS, the 6MWD is a valid and responsive measure of functional capacity. The MID will facilitate planning and interpretation of future group comparison studies in this population.